Letter from Max Bredig to Kasimir Fajans, September 3, 1937 - Bredig, Max Albert (1937)
In a letter to Kasimir Fajans (1902-1977), Max Bredig (1902-1977) discusses preparations for his move to Ann Arbor, Michigan, including travel plans and accommodations.
Keywords: Bredig, Max Albert, 1902-1977; Fajans, Kasimir, 1887-1975; Michigan--Ann Arbor; Emigration and immigration